Blockade of mitochondrial calcium uniporter prevents cardiac mitochondrial dysfunction caused by iron overload - Sripetchwandee J. (2014)
Aim: Iron overload in the heart can lead to iron-overload cardiomyopathy and cardiac arrhythmia. In the past decades, growing evidence has suggested that cardiac mitochondrial dysfunction is associated with the development of cardiac dysfunction and lethal arrhythmias. Despite these facts, the effect of iron overload on cardiac mitochondrial function is still unclear. In this study, we determined the effects of iron overload on the cardiac mitochondrial function and the routes of cardiac mitochondrial iron uptake. We tested the hypothesis that iron overload can lead to cardiac mitochondrial dysfunction and that mitochondrial calcium uniporter (MCU) plays a major role for cardiac mitochondrial iron uptake under iron-overload condition. Cardiac mitochondrial function was assessed via the determination of mitochondrial swelling, mitochondrial reactive oxygen species (ROS) production and mitochondrial membrane potential changes. Methods: Isolated cardiac mitochondria from male Wistar rats were used in this study. To determine the routes for cardiac mitochondrial iron uptake, isolated mitochondria were exposed to MCU blocker (Ru360), mitochondrial permeability transition pore (mPTP) blocker (cyclosporin A) and an iron chelator (deferoxamine). Results: We found that (i) iron overload caused cardiac mitochondrial dysfunction, indicated by increased ROS production, mitochondrial membrane depolarization and mitochondrial swelling; and (ii) only MCU blocker completely protected cardiac mitochondrial dysfunction caused by iron overload. Conclusions: These findings strongly suggest that MCU could be the major route for iron uptake into cardiac mitochondria. The inhibition of MCU could be the novel pharmacological intervention for preventing iron-overload cardiomyopathy. © 2013 Scandinavian Physiological Society.